Cell Kinetics and siSTEAP4 Responses - Gonen, Ceren (British Journal of Healthcare and Medical Research, 2025)
STAMP family genes STAMP1/STEAP2 and STAMP2/STEAP4 have only expressed in androgen receptor-positive cells, the role of AR in STAMP family gene expression is an important question.